SURVIVAL STRATEGY OF STREET MUSICIAN IN TAMPAN DISTRICT PEKANBARU - Toni Pardede; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research carried out in Tampan District, Pekanbaru. This research aims to determine the characteristics and survival strategies of street musician. To obtain the necessary data in this study, the writer collected data to descend directly to the research location and do observation and in-depth interviews. The subjects of this research as many as seven person. Data obtained was processed in the descriptive qualitative analysis form. Technique determination sample of research using incidental sampling technique that is obtained with no premeditation but by chance. Conclusions from this research that the majority of subjects who became a street musician is new comers in Pekanbaru are having trouble finding a job overseas especially coupled with low education level. The majority of subjects come from West Sumatera as many as three person, while in Medan and Pekanbaru each two person. The education level subjects who graduated high school and junior school each three person and who graduated in elementary school only 1 person. Besides that, to survive, street musician using three strategies, namely active, passive and network strategy. Active strategy doing a side job as a internet guard, builder, sellers of used goods, and parking attendants. Passive strategy is to minimize expenditure, take potluck, buying used clothing and go to clinic when they sick. Networking strategy is to utilizing a school helps for poor student, so as to finance the needs of education and borrow money when they need suddenly to neighbors or family. High competition of life is the reason for choosing job as musician street. Limitation of job require subjects to work on the streets and relying busking for a living in order to life necessities. When took to the road, street musician always be worry to the presence of the civil service police unit. Even to avoid, street musician always, wary chase with officers. Music quality in each subject are also different, because the street musician do not have to be good at singing or playing music, but as a subject can entertain people at the location where they singing. Income earned is determined by the situation of the road, weather conditions and the quality of entertainment given. If the condition of income support, street musician in a day could reach Rp. 50.000.Keywords : Survival strategy, Street musician